2011
DOI: 10.2215/cjn.03840510
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association of Depressive Symptoms with Rapid Kidney Function Decline and Adverse Clinical Renal Disease Outcomes

Abstract: SummaryBackground and objectives Depression is a risk indicator for adverse outcomes in dialysis patients, but its prognostic impact in individuals who are not yet on dialysis is unknown. This study examines whether depressive symptoms are longitudinally associated with renal function decline, new-onset chronic kidney disease (CKD), ESRD, or hospitalization with acute kidney injury (AKI).Design, setting, participants, & measurements Depressive symptoms were measured in a longitudinal cohort study with the 10-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 57 publications
7
80
2
1
Order By: Relevance
“…In the largest prospective CKD cohort to date, Fischer et al (34) found that depressive symptoms in the Chronic Renal Insufficiency Cohort Study were associated with a 21% higher risk of CKD progression over 5 years. However, the Cardiovascular Health Study (CHS) did not find an association between depressive symptoms and incident ESRD in their community-based cohort of elderly participants (17). This discrepancy may be related to the low prevalence of CKD in the study population in the CHS and, therefore, a lower incidence of ESRD (,2%) compared with the CKD cohorts in the other studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the largest prospective CKD cohort to date, Fischer et al (34) found that depressive symptoms in the Chronic Renal Insufficiency Cohort Study were associated with a 21% higher risk of CKD progression over 5 years. However, the Cardiovascular Health Study (CHS) did not find an association between depressive symptoms and incident ESRD in their community-based cohort of elderly participants (17). This discrepancy may be related to the low prevalence of CKD in the study population in the CHS and, therefore, a lower incidence of ESRD (,2%) compared with the CKD cohorts in the other studies.…”
Section: Discussionmentioning
confidence: 94%
“…However, these studies were conducted in patients with a high likelihood of progression to ESRD because of preexisting CKD. In contrast, depressive symptoms were not predictive of incident ESRD in the Cardiovascular Health Study, a community-based cohort of individuals with a low likelihood of ESRD incidence (17). These discrepancies in findings may be attributable to differences in the underlying study populations, baseline levels of CKD, participant risk for ESRD, and definitions of ESRD.…”
Section: Introductionmentioning
confidence: 87%
“…Several of these problems individually have been shown to be associated with kidney disease (15)(16)(17). For example, an association between kidney disease and cognitive impairment has been consistently shown in previous studies (18)(19)(20).…”
Section: Introductionmentioning
confidence: 69%
“…In a previous analysis of the REGARDS Study, an 11% increase in the odds of prevalent cognitive impairment was shown for every 10-ml/min per 1.73 m 2 incremental decrease in eGFR (18). Depressive symptoms have also been evaluated in association with reduced eGFR (16). Exhaustion, a key component of the frailty phenotype, has been reported to be more prevalent at lower levels of reduced eGFR (26).…”
Section: Discussionmentioning
confidence: 99%
“…Some other investigators observed that serum urea, creatinine and uric acid levels were significantly increased after 2 weeks treatment with oxidative stress induced by mercuric chloride(0.5 mg/ kg bw) 9 .In a longitudinal study (5days to 11 years)it has been shown that the individuals with depressive symptoms may develop rapid declines in kidney function and hospitalization occur with acute kidney injuryduring follow-up 10 .…”
Section: Introductionmentioning
confidence: 99%